Phosphatase UBLCP1 controls proteasome assembly. Issue 5 (24th May 2017) - Sun, Shuangwu; Liu, Sisi; Zhang, Zhengmao; Zeng, Wang; Sun, Chuang; Tao, Tao; Lin, Xia; Feng, Xin-Hua
Abstract : Abstract : Ubiquitin-like domain-containing C-terminal domain phosphatase 1 (UBLCP1), an FCP/SCP phosphatase family member, was identified as the first proteasome phosphatase. UBLCP1 binds to proteasome subunit Rpn1 and dephosphorylates the proteasome in vitro . However, it is still unclear which proteasome subunit(s) are the bona fide substrate(s) of UBLCP1 and the precise mechanism for proteasome regulation remains elusive. Here, we show that UBLCP1 selectively binds to the 19S regulatory particle (RP) through its interaction with Rpn1, but not the 20S core particle (CP) or the 26S proteasome holoenzyme. In the RP, UBLCP1 dephosphorylates the subunit Rpt1, impairs its ATPase activity, and consequently disrupts the 26S proteasome assembly, yet it has no effects on the RP assembly from precursor complexes. The Rpn1-binding and phosphatase activities of UBLCP1 are essential for its function on Rpt1 dephosphorylation and proteasome activity both in vivo and in vitro . Our study establishes the essential role of the UBLCP1/Rpn1/Rpt1 complex in regulating proteasome assembly.